An iteration procedure for solving integral equations related to optimal stopping problems - Denis Belomestny; Pavel V. Gapeev (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
A new algorithm for finding value functions of finite horizon optimal stopping problems in one-dimensional diffusion models is presented. It is based on a time discretization of the corresponding integral equation. The proposed iterative procedure for solving the discretized integral equation converges in a finite number of steps and delivers in each step a lower or an upper bound for value of discretized problem on the whole time interval. The remarks on the application of the method for solving integral equations related to some optimal stopping problems are given.
Keywords: 330